(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Since we cannot imagine a world without energy, and since numerous studies have demonstrated that fuel consumption at our current level is unsustainable and harmful to the planet, it is imperative to take this into account when designing any system. As fossil fuels are often the only or primary source of energy in many nations, there is no need to completely eliminate their use. It is instead necessary for technology efficiency to be enhanced, clean energies to grow, and consumption to be lowered in order to achieve a generational balance. In this situation, it was decided to construct a miniature wind rotor that would work as a teaching aid for engineering students. A computer-programming model has been created to build the turbine that, based on simplified nautical ideas, enables calculating the geometry of the blades depending on some beginning conditions, estimating the rotor power, and determining the operating curves for the rotor.